A brief review: Multimedia authoring modeling - Wijaya, Marvin Chandra; Maksom, Zulisman; Abdullah, Muhammad Haziq Lim (Taiwan Ubiquitous Information CO LTD, 2022)
Multimedia Authoring is a way to develop a multimedia presentation. Multimedia content includes images, sounds, videos, texts, and animations. The Kernel Mechanism of Multimedia Authoring consists of the Multimedia Authoring Programming Language and the Multimedia Authoring Model. Multimedia Authoring modeling is designed to enable the Multimedia Authoring function appropriately. Since the beginning of designing multimedia authoring tools, various studies were conducted to create a multimedia authoring model. Multimedia Authoring models that have been studied in existing research are Petri Nets, Hoare Logic, and LOTOS. The three models use different approaches. Petri Net uses a model based on graph calculations, Hoare logic uses mathematical logic, and LOTOS uses a formal specification language. Each of these models has been developed and modified to have higher capabilities. This model modification has advantages over the original model. This review article discusses the development and modifications of these models.